2015
DOI: 10.1111/1754-9485.12294
|View full text |Cite
|
Sign up to set email alerts
|

Use of implanted gold fiducial markers with MV‐CBCT image‐guided IMRT for pancreatic tumours

Abstract: These data suggest that fiducial markers used in conjunction with MV-CBCT improve the accuracy of daily target delineation compared with localisation using adjacent bony anatomy and that gold fiducial markers using MV-CBCT alignment are a viable option for target localisation during IG-IMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Without the fiducial marker, it is quite difficult to distinguish the pancreatic tumor from surrounding normal organs such as stomach and duodenum on cone beam CT for IGRT because of the movement or gas from gastrointestinal organs. Several reports demonstrated that marker matching is better than bony structure matching for pancreatic cancer [ 16 , 17 ]. Considering that the fiducial marker is beneficial to be implanted for IGRT for pancreatic radiotherapy if it is not DTT-IMRT, indispensability of fiducial marker for DTT-IMRT is not a specific weak point.…”
Section: Discussionmentioning
confidence: 99%
“…Without the fiducial marker, it is quite difficult to distinguish the pancreatic tumor from surrounding normal organs such as stomach and duodenum on cone beam CT for IGRT because of the movement or gas from gastrointestinal organs. Several reports demonstrated that marker matching is better than bony structure matching for pancreatic cancer [ 16 , 17 ]. Considering that the fiducial marker is beneficial to be implanted for IGRT for pancreatic radiotherapy if it is not DTT-IMRT, indispensability of fiducial marker for DTT-IMRT is not a specific weak point.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the respiratory motion of the target mass during radiation therapy, the placement of fiducials has been related to better targeting compared with localization using adjacent bony anatomy. [ 16 17 ]…”
Section: The Role Of Radiation Therapy In Gastrointestinal Malignanciesmentioning
confidence: 99%
“…Studies have shown that fiducial markers improve the accuracy of target delineation during SBRT when compared with localization by the use of adjacent bony anatomy 9, 10, 11. Fiducial tracking is typically preferred when available.…”
Section: Role Of Fiducial Markers In Sbrtmentioning
confidence: 99%